THE SPECIFICS OF ADOLESCENT CRISIS DURING THE COVID-19 PANDEMIC - Dukanac, Vesna; Ljubomirovic, Natasa; Dukanac, Dusica (HEALTH CARE, 2020)
Introduction/Aim: Adolescents pass through three phases of an accidental crisis: the negation of real danger, feeling of confusion and chaos with the onset of the first symptoms, a complete depressive breakdown with a different range of manifestations. The Covid-19 pandemic has become a real challenge for these patients. The aim of this study is to review and analyze the clinical psychotherapeutic material of the described phases of the passage through the accidental crisis, caused by the Coronavirus pandemic. Methods: Adolescents of different ages are involved. The materials of psychotherapeutic sessions of adolescents were used in the paper, from different phases of the adolescent crisis. To explain the phase of negation of real danger, adolescents of the early and central stages of a period of adolescence are presented. To explain the phase of feelings of confusion and chaos to complete depressive breakdown, adolescents of the late and post adolescent stages of a period of adolescence are presented. Patient presentation: In adolescents, who did not show a problematic passage through the developmental crisis, the accidental crisis of the pandemic leads to the denial of the real danger. In a younger, twelve-year-old adolescent, at a specific level of functioning, there is a weakened concentration for learning. In a slightly older, fifteen-year-old adolescent, the denial of real danger, through sublimation, goes into altruism. In adolescents with already manifested problematic passage through the developmental crisis, the symptoms worsen due to the effect of the superimposed accidental crisis caused by the pandemic. In adolescents, the middle phase of adolescence, there is a mixture of real somatic problems with somatization. In the older adolescent, post adolescent phase, with addiction disease problems, the pandemic provokes irritability and low frustrating tolerance leading to complete depressive breakdown. Conclusion: We can conclude that the superposition of accidental crises always complicates the normative adolescent crisis, but we emphasize that the manifested psychopathology can be of a transient character. Psychiatric psychotherapeutic interventions are determined in relation to the degree of threatening or completely manifested decompensation from shorter counseling interventions to the intensification of deep psychotherapy, with or without adequate drug therapy.